Parent-Adolescent Communication and Early Adolescent Depressive Symptoms: The Roles of Gender and Adolescents’ Age - Zhang, Qiongwen; Pan, Yangu; Zhang, Lei; Lu, Hang (Frontiers in Psychology, 2021)
Positive parent-adolescent communication has been found to be negatively related to adolescent depressive symptoms; however, few studies have investigated the moderating effects of adolescent gender and age on this relationship, especially during early adolescence in China. The present study investigated the joint moderating effects of adolescent gender and age on the linkage of father-adolescent and mother-adolescent communication with adolescents’ depressive symptoms. A total of 11455 Chinese junior high school students (Mage = 14.15 years, SD = 1.22 years; 49.86% boys; Ngrade7 = 5712, Ngrade9 = 5743) completed ad hoc questionnaires of parent-adolescent communication and depressive symptoms. Multiple linear regression analyses were conducted. Results indicated that gender and age jointly moderated the association between parental communication and adolescent depressive symptoms. Specifically, for girls, the negative effects of both father-adolescent and mother-adolescent communication on depressive symptoms were stronger in 9th grade students than in 7th grade students, while for boys, the negative effects were not different between 7th grade students and 9th grade students. These findings suggest that in China, the protective effects of positive parent-adolescent communication on adolescents’ depressive symptoms may be most salient among senior-grade girls in junior high school.